Return and Risk Comparative Analysis in the Formation of Optimal Share Portfolio with Random Model, Markowitz Model, and Single Index Model - Abdul Muslim (Institut Ilmu Sosial dan Manajemen STIAMI, 2020)
This research was conducted to determine the composition of the stock portfolio formed by the Random model, the Markowitz model, and the Single Index model and which portfolio composition was optimal from the results of calculations using the Random model, the Markowitz model, and the Single Index model. The method used is a quantitative analysis using stock price data in the LQ45 Index group listed on the Indonesia Stock Exchange (IDX). In the first random process the results of calculating the expected return value for each share and obtained portfolio candidates can produce a total expected return of 0.2726 or 27.26%. The Markowitz method produces 14 shares that have a positive value, which means it enters into portfolio-forming shares, while the Single Index Model obtains diversified investments in the form of a portfolio of 6 shares